Implementasi Program â€œKeluar Bersamaâ€ dalam Inovasi Pelayanan Publik di Kecamatan Danurejan Kota Yogyakarta - Munawaroh, Siti; Mutiarin, Dyah (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2019)
This research discuss about innovation ?Keluar Bersama? in Danurejan Subdistrict Yogyakarta City. The research was carried out with the aim of finding out the implementation of the "Keluar Bersama" program in public service innovations. The problem in this study is that after the "Keluar Bersama" program there was still a significant difference between the ownership of Birth Certificates which reached 95%, while Child Identity Card only reached 62%. The creation of this innovation is the integration between 1 document and other documents, so there should be a similarity in the number of documents made. Thus, this study will look at the implementation of this "Keluar Bersama"  innovation. The type of research used is mixed methods research, with data collection techniques using questionnaires, observation, and documentation. The results of this study are seen from implementation of innovation ?Keluar Bersama? by the Danurejan Subdistrict society seen from Public Governance, the society responded positively, this was influenced by the society participation in innovation, the ease of accessing information was also facilitated. The Danurejan Subdistrict Government is quite transparent in providing services, and is also accountable in carrying out its duties. Whereas for the aspect of utilizing public services getting good value because the innovation ?Keluar Bersama? is able to overcome population administration problems, the technology used in innovation is also easy to use by the society.  In addition, the innovations ?Keluar Bersama? also able to simplify, facilitate services, benefit to society, also increases service productivity and effectiveness.